Ideación suicida y respuestas rumiativas en estudiantes de pregrado de una universidad privada en Cartagena (2017)
The paper entitled "Suicidal Ideation and Rumitive Responses in Undergraduate Students at a Private University in Cartagena," describes suicidal ideation and ruminant responses, while determining how these variables are directly related to suicidal acts in students. This project is based on studies by Beck, A. (1973) Seligman (1986), Ellis T, (2008) and Nolen-Hoeksema. Has the general objective: To describe the suicidal ideation and the ruminative answers in students of undergraduate of a Private University in Cartagena. And Specific Objectives To identify the presence of suicidal ideation in undergraduate students of a private university in Cartagena Identify the presence of ruminative response style in undergraduate students from a private university in Cartagena. Relate the suicidal ideation and the ruminative responses in undergraduate students of a private university in Cartagena. The approach of the present investigation is of quantitative type, since it has quantifiable values, it tries to take objective measurement of a social reality.